Incentive Contract in Supply Chain with Asymmetric Information - Yingsheng Su; Hongmei Guo; Xianyu Wang (Discrete Dynamics in Nature and Society)
The supply chain always appears inefficient because of the different targets of members and information asymmetry, especially when upstream enterprises not only hide information about their effort levels, but also hide information about their technology level. The paper uses principal-agent theory and the theory of regulation to design the contract to realize the maximization of principal's profit on the condition that the contract satisfies the participant and incentive conditions of agent. As a result, it is obvious that the contract achieves the goal of control. In addition, it also can be concluded that the amount of rent that the manufacturer can obtain is up to the value of his information and the condition of his resource.